Performance and bone quality of broiler chicken fed a diet with reduced nonphytate phosphorus with bacterial phytases - Dos Santos, Tatiane Souza [UNESP]; Denadai, Juliana Célia [UNESP]; Sartori, Maria Márcia Pereira [UNESP]; Júnior, João Martins Pizauro [UNESP]; Aoyagi, Mônica Megumi [UNESP]; Rezende, Juliana Cristina Ramos [UNESP]; Serpa, Paola Gentile [UNESP]; Muro, Everton Moreno [UNESP]; de Santana-Eich, Mayara Rodrigues [UNESP]; Pasquali, Guilherme Aguiar Mateus [UNESP]; Dornelas, Lívia Carrasco [UNESP]; Netto, Raimundo Gonçalves Ferreira [UNESP]; et al. (Canadian Science Publishing, 2019)
This study evaluated the effect of three phytases in reduced nonphytate phosphorus (NPP) diets. In total, 2100 male Cobb 500® chicks were distributed in a completely randomized design. Ten experimental diets were used: NPP1 reduction of 0.12% NPP plus phytase A, B, C, or without; NPP2 reduction of 0.22% NPP plus phytase A, B, C, or without; positive control diet, attending nutrient requirements; negative control diet, deficit of 0.10% NPP. The 2 × 4 + 2 (two levels NPP, three phytases or without, and two controls) design was used, and the means were compared by Tukey’s or Dunnet’s (p < 0.05) tests. There were significant interactions on day 21 for weight gain (p < 0.01), feed conversion ratio (p < 0.01), and day 35 for weight gain (p < 0.01), feed intake (p < 0.01), feed conversion ratio (p < 0.01), European production efficiency factor (p < 0.01), and it was shown that three phytases in NPP1 diet had the same result as positive control (PC) diet. NPP2 diets without phytase promoted high calcium (p < 0.01) and low phosphorus (p < 0.01) in plasma, and the significant interaction showed higher activity for alkaline phosphatase (p = 0.023). The significant interactions for resistance (p = 0.001) and ash (p < 0.01) of femur indicate that inclusion of phytases in diet NPP1 improved the availability of minerals, suggesting that this reduction plus phytase would be enough for better results.
Keywords: Ash; Calcium; Densitometry; Phosphorus; Resistance